Investigating the In-vitro Anti-helminthic Activity of Hydroalcoholic Extract of Martynia annua L. and Pentanema indicum - Gayathiri N. M.; Sudhakar P.; Sabarinath C.; Poorana Pushkalai S.; Kalaivani H. (Pharmaceutical Research: Recent Advances and Trends Vol. 6, 2024)
Background: Helminthiasis or worm infestation, is one of the most prevalent diseases. According to the World Health Organization, infectious diseases are the main cause of death and the key agents of afflicting worldwide. Modern anti-helminthics have limited the effective control of the parasites due to a number of side effects and the development of resistance in helminths. This renewed the interest in screening medicinal plants for their anti-helminthic activity. Objective: The present study was designed to investigate the In vitro anthelmintic activity of hydroalcoholic extract of Martynia annua L. and Pentanema indicum. Methods: Martynia annua and Pentanema indicum were collected from the local areas of the region of Chitharampoondi, Erode. Nine groups each containing three adult Indian earthworms (Phentanema posthuma) of approximately the same size were received into 20ml of the desired formulation. Group I was treated with normal saline and group II was treated with albendazole (20 mg/ml) in 1% w/v of CMC as standard and III, IV, and V groups were concentrations of hydroalcoholic extracts of Martynia annua L. 10, 20, 50 mg/ml and VI, VII and VIII group was concentrations of hydroalcoholic extracts of Pentanema indicum 10,20,50mg/ml in 1% w/v of CMC. The last ninth group was treated with a combination of Martynia annua L. and Pentanema indicum (50 mg/ml and 50 mg/ml). Results: Both the extracts show a dose-dependent reduction in paralysis and death time of the worm, the combination of Martynia annua L. and Pentanema indicum 1:1 ratio extract was found to be more effective, especially at 50 mg/ml and 50 mg/ml. The results were compared with the standard drug, Albendazole and it was found that both extracts were more effective than the selected standard drug. Conclusion: The anti-helminthic activity of extracts was comparable to standard Albendazole, and could be effective against parasitic helminths of humans and animals. The presence of alkaloids, flavonoids, tannins, and phenol in the extracts may be contributory to its anti-helminthic activity. Further study is required with the selected plant for the development of novel standardized anthelmintic herbal formulations.